(untitled) (Bangladesh Journal of Botany, 2019)
Effect of polyamine (putrescine) and mycorrhiza combination on putrescine and mycorrhiza responsiveness index was studied in sorghum. It is evident that the average putrescine and mycorrhiza responsiveness index was non-significantly enhanced by 48.40, 48.43 and 46% when exposed to higher dose of polyamine (putrescine) and mycorrhiza combination (T5) as compared to lower dose of polyamine (putrescine) and mycorrhiza combination (T4) at 30, 60 and 90 DAS of interval. Similarly, when plants were exposed to higher dose of polyamine (putrescine) and mycorrhiza combination (T11) than its putrescine and mycorrhiza responsiveness index was non-significantly enhanced by 11.03, 13.22 and 13.18% as compared to T10. When treatment, T17 was compared to T16, the putrescine and mycorrhiza responsiveness index increased significantly by 7.13, 6.73 and 5.35% at proposed DAS. So, the combination of putrescine and mycorrhiza showed the best combination for the mitigation of cadmium toxicity for the putrescine and mycorrhiza responsiveness index.